Assessment on the antioxidant, photoprotective, and antimicrobial properties of Siraitia grosvenorii - Figo, Figo; Candra, Tasya Mariska; Novia, Jessica; Sugata, Marcelia (JURNAL ILMU KEFARMASIAN INDONESIA, 2025)
Exogenous antioxidants from plant-based sources, such as polyphenols, show potential in maintaining a balance of cellular oxidation in biological systems. Additionally, the rise of antimicrobial resistance and the harmful effects of UV radiation on skin necessitate the exploration of medicinal plants for drug development and photoprotective agents. This study specifically focused on Siraitia grosvenorii or Luo Han Guo, and aimed to assess its phenolic and flavonoid content, as well as its antioxidant, antimicrobial, and photoprotective properties. The study involved the preparation of Siraitia grosvenorii extracts from seeds and fruit peels, determination of total phenolic and flavonoid content using Folin-Ciocalteu reagent and AlCl3, evaluation of antioxidant activity using the DPPH method, and analysis of antimicrobial activity against Escherichia coli using turbidity assays. Photoprotective activity was examined by calculating the Sun Protection Factor (SPF) using a UV spectrophotometer and a normalized function. The results showed that fruit peel of Siraitia grosvenorii had a higher total phenolic content than the seed, and no significant difference in flavonoid content between seed and fruit peel extract. Additionally, Siraitia grosvenorii fruit peel and seed had low SPF value and DPPH reduction. Both fruit peel and seed showed highest antimicrobial activity at the concentration of 100 ppm.